2019
DOI: 10.1186/s40494-019-0254-1
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced procedure for the analysis of organic binders in Pompeian’s wall paintings from Insula Occidentalis

Abstract: Quantitation of paint powders of ancient wall paintings is often hindered by the calcite contamination during samples withdrawal. To overcome this problem, a new approach was explored based on the mechanical pulverization of the paint powder followed by the evaluation of its true concentration, namely binders, pigments, and decaying compounds, from the comparison of the calcite FT-IR peak area at 2510 cm −1 with that of the corresponding underlying calcite used as calibrator. After extraction of the pulverized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As already discussed in previous studies [6,24,47], several factors may limit the capability of the FTIR technique to accurately identify the presence of organic materials in ancient wall painting samples, such as the low concentration of the binder and the strong absorption of the inorganic matrix (that gives rise to wide bands associated with distortions). In order to accurately assess the presence of an organic binder, refined procedures or more sensitive techniques need to be employed [16,54,55]. The use of remote non-invasive techniques capable of investigating larger and targeted areas will also be taken into account in future studies [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…As already discussed in previous studies [6,24,47], several factors may limit the capability of the FTIR technique to accurately identify the presence of organic materials in ancient wall painting samples, such as the low concentration of the binder and the strong absorption of the inorganic matrix (that gives rise to wide bands associated with distortions). In order to accurately assess the presence of an organic binder, refined procedures or more sensitive techniques need to be employed [16,54,55]. The use of remote non-invasive techniques capable of investigating larger and targeted areas will also be taken into account in future studies [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Mills [65] also showed that the ratio of palmitic/stearic acid is stable over time and can be used for oil identification. Later, several studies confirmed it [63,67,68], except for Tammekivi et al [51] and some others, who emphasized using other criteria for confirmation. Still, according to Tammekivi et al [51], the concentration of the particles (pigments) has a substantial impact on the fatty acid correlated to drying oils.…”
Section: Sample Bindersmentioning
confidence: 98%
“…A study of Corso et al has employed spectroscopic, techniques and GC coupled to flame-ionization detector to study binders of a mural painting fragment from Liternum (Italy) archaeological excavation [74]. The results obtained were compared with those obtained from the examination of collected samples in Pompeii from "Imperial Villa, Insula Occidentalis" suggesting that in both cases tempera painting with binders of animal origin had been used [75,76].…”
Section: Invasive Techniquesmentioning
confidence: 99%